Performance analysis of SAW gas sensor based on ST-Cut quartz for breath analysis - Mohamad Razali, Nur Fatin; Md Ralib @ Md Raghib, Aliza 'Aini; Ab Rahim, Rosminazuin (Institute of Electrical and Electronics Engineers, Inc., 2018)
Abstract- Breath analysis is the recent technique used to detect diseases. Among the advantages of breath analysis are high sensitivity and fast detection. Surface acoustic wave (SAW) gas sensor is one of the sensors that can be used to analyze breath analysis. This work reports on the design and simulation of SAW gas sensor using a FEM simulator, COMSOL Multiphysics. We analyze the possibilities of increasing the quality factor, coupling coefficient and the wave velocity of the devices by varying the number of interdigitated electrodes (IDTs). We designed and simulated IDTs pf different finger number (IDT= 2, 4, 8, 12, 16, 20, 24, 28 and 32). The measured quality factor, coupling coefficient and wave velocity confirms that varying the number of IDTs fingers enables to reach better electrical performances at resonances frequency around 943 MHz.